(untitled) (Revista de Estudos da Linguagem, 2024)
In this work, we intend to delve into the importance of using cognitive linguistics tools to describe and explain the functioning of discourses from a critical perspective. In particular, we analyse the way in which the concepts of frames, metaphors, metonyms and image schemes can be used productively for the analysis of the verbal mode and manual gestures. In order to do this, we analyse an interview that former Chilean President Sebastián Piñera gave in 2016 during the campaign prior to his re-election. We conclude that certain manual gestures carry ideational meaning and reinforces discursive strategies present in the verbal mode.